Global research trends in extracellular vesicles based on stem cells from 1991 to 2021: A bibliometric and visualized study - Lin, Jianjing; Yang, Zhen; Wang, Li; Xing, Dan; Lin, Jianhao (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: With the development of extracellular vesicles (EVs) based on stem cells research all over the world, our present study was aiming to discover the global trends in this field. Methods: All publications related to EVs based on stem cells from 1991 to 2021 were collected from the Science Citation Index-Expanded of Web of Science (WoS). Subsequently, the data were evaluated using the bibliometric methodology. In terms of visualized study, the VOS viewer software was performed to investigate the bibliographic coupling, co-citation, co-authorship, and co-occurrence trends, and last for the publication’s trends involved in the field of EVs based on stem cells. Results: A total of 8208 publications were retrieved and the relative number of global publications and research interests were increasing every year especially in recent 5 years. China rank top 1 in terms of total publications, prolific authors, and funds, whereas the USA made the greatest contributions with the most total citations and highest H-index to the global research. Stem cell research therapy contributed the highest publications, whereas the journal of PLOS ONE showed the best total link strength. The Shanghai Jiao Tong University, University of California System, and Harvard University were the most contributive institutions. The global studies could be divided into six clusters as follows: cancer research, musculoskeletal system research, respiratory system research, urinary system and endocrine system research, nerve system research, and cardiovascular system research. All the directions were predicted to still hotspots in near future researches in this field. Conclusions: The total number of publications about EVs based stem cells would be increasing according to the current global trends. China and the USA was the largest contributors in this field. Further efforts should be put in the directions of cancer research, musculoskeletal system research, respiratory system research, urinary system and endocrine system research, nerve system research, as well was cardiovascular system research in this field of EVs based stem cells.